Efeitos da farinha liofilizada da polpa de bocaiúva (acrocomia aculeata) sobre parâmetros metabólicos e oxidativos em ratos - Correia, Francyele dos Santos (2020)
Acrocomia aculeata, known as macaúba or bocaiúva, can be found in much of the Brazilian territory, being abundant in the Midwest region, especially in Mato Grosso and Mato Grosso do Sul. The pulp of the fruit is consumed fresh or in the form of oil and used for food and cosmetic purposes. As a herbal medicine, bocaiúva has been popularly used as a fortifier, analgesic, hypoglycemic, in the control of total cholesterol, laxative, anti-inflammatory and diuretic and many of these effects are still under investigation. In this context, the objective of this work was: a) to determine the proximate composition of the bocaiúva pulp, the concentration of some classes of bioactive compounds present in it and its antioxidant potential, in vitro and; b) evaluate the effects of consumption of lyophilized bocaiúva flour on metabolic and oxidative parameters in Wistar rats. For this, male Wistar rats (~ 200g) were used, which were randomly divided into 3 groups: Control Group (C), Supplemented Group 250 (S250) and Supplemented Group 500 (S500). Group C received vehicle (water), orally by gavage technique, while groups S250 and S500 received the aqueous extract of bocaiúva flour at a concentration of 250 and 500 mg / kg of the animal, respectively. The supplementation lasted 28 days and the animals of all groups were fed with Labina® commercial feed. At the end of the experiment, the animals were anesthetized and killed by decapitation. Blood, tissues and carcass were collected for biochemical, metabolic and oxidative analysis. Data were presented as mean ± standard error (ANOVA-1via or Test t; p <0.05). The bocaiúva pulp used in this study showed 41.3% water, 18.0% lipids, 2.3% ash, 5.8% protein, 32.7% carbohydrates and an energy value of 13.2 KJ/g of pulp. In addition, it exhibited concentrations of 50.0mgEAG/100g and 32.3mgERU/100g of phenolic compounds and total flavonoids, respectively. The EC50 of the ethanolic extract of the bocaiúva pulp (17.7 mgEAG/L), determined by the sequestration of the free radical DPPH, was 29% lower than that of the butylhydroxytoluene standard (24.8 mg/L). It was observed that the S500 group ate more food than the other groups (10% more than group C and 9.1% more than group S250), which resulted in an increase in energy intake of 17% compared to group C and 12% in relation to group S250. The hepatic lipid content was 29.7% and 34.5% higher in animals in the S500 group when compared, in that order, to groups C and S250. The carcass composition showed a 30% reduction in protein content in the S500 group compared to the S250 group, while the lipid content in the S500 group was 57% higher compared to group C and 111% compared to the S250 group. The carcass energy of the S500 group increased significantly by 18% and 11% when compared to groups C and S250, respectively. The energy gain of the S500 group increased 36% when compared to the C group and 52% when compared to the S250 group. The hepatic content of PPAR-α and PPAR-γ transcription factors were reduced (40% and 44%, respectively) in animals in the S500 group, when compared to group C. Regarding the biochemical parameters, the glucose concentration in the fed state of the animals in the S500 group it was 10% higher when compared to group C and the plasma urea concentration decreased by 21% compared with the same group. The area under the TTGO curve was 12% greater in the S500 group compared to the S250 group. From the oxidative parameters evaluated, there was a 32% reduction in the concentration of carbonylated proteins measured in the liver of animals in the S500 group compared to group C. The liver activity of the GPx enzyme increased 62% in the S250 group and 64% in the S500 group, compared to group C. The activity of GR in this tissue was increased in the S250 group (49% higher compared to group C and 46 % higher in relation to the S500 group). The activity of the SOD and CAT enzymes, respectively, were 79% and 80% higher in the S500 group compared to the C group. The S250 group also showed a 70% increase in CAT activity compared to group C. The content of the factor of Nrf2 transcription in the liver of animals in the S500 group was 116% compared to group C. There were no statistical differences in the other parameters evaluated. The results of this study demonstrate that the intake of bocaiuva flour for 28 days, in the highest dose, led to several changes in the metabolism of carbohydrates and lipids (evidenced by changes in the content of lipids, in the transcription factors PPAR-α and PPAR-γ , changes in blood glucose and TTGO), suggesting the induction of a condition similar to that of non-alcoholic fatty liver disease and oral glucose intolerance. On the other hand, the data suggest an improvement in the oxidative status in the liver of animals that received bocaiúva flour, demonstrated by the induction of antioxidant enzymes and an increase in Nrf2 content. However, further investigations are needed to confirm or reject this hypothesis.